Welcome to the revolution managing paradox in the 21st century - Cannon, Tom, B. Sc (Pitman Pub., 1996)
This text highlights the best ways managers, firms and societies can adapt to exploit the opportunities and avoid the dangers inherent with change. It examines how the 21st century will appear to managers and corporations and what they will have to do to be winners. Based around the Institute of Management's Management in the Millennium Report by Tom Cannon, which identifies the nine main paradoxes facing managers in the 21st century, the book shows how these paradoxes will affect the business of companies and the lives of managers.